Analisis Keuntungan Usaha Kacang Sangrai UD. Merpati Di Desa Tombasian Atas Kecamatan Kawangkoan Barat - Mundung, Fabio G.B.; Kapantow, Gene Henfried Meyer; Tangkere, Ellen Grace (Sam Ratulangi University, 2024)
This study aims to analyze the profitability of the roasted peanut industry at UD. Merpati in Tombasian Atas Village. The research lasted for three months from June to August 2023. The research was conducted at Merpati Roasted Peanuts, Tombasian Atas Village, West Kawangkoan District. Data collection methods used in this study were obtained through primary data and secondary data. Data analysis used in this research is business profit analysis, then the data collected is described descriptively to determine the amount of production costs incurred from the business being run. The results showed that UD Merpati roasted peanuts have 3 types of packaging with different prices and for the price installed with 250 gr packaging with a selling price of IDR20.000 while for 400 gr packaging with a selling price of IDR 30,000 and for 800 gr packaging has a selling price of IDR60.000. UD roasted peanut business. Merpati despite the increase in raw material prices obtained good results with a profit of IDR41.463.194.